Profiling molecular and behavioral circadian rhythms in the non-symbiotic sea anemone Nematostella vectensis - Oren, Matan (Sci Rep, 2015)
Endogenous circadian clocks are poorly understood within early-diverging animal lineages. We have characterized circadian behavioral patterns and identified potential components of the circadian clock in the starlet sea anemone, Nematostella vectensis: a model cnidarian which lacks algal symbionts. Using automatic video tracking we showed that Nematostella exhibits rhythmic circadian locomotor activity, which is persistent in constant dark, shifted or disrupted by external dark/light cues and maintained the same rate at two different temperatures. This activity was inhibited by a casein kinase 1δ/ε inhibitor, suggesting a role for CK1 homologue(s) in Nematostella clock. Using high-throughput sequencing we profiled Nematostella transcriptomes over 48 hours under a light-dark cycle. We identified 180 Nematostella diurnally-oscillated transcripts and compared them with previously established databases of adult and larvae of the symbiotic coral Acropora millepora, revealing both shared homologues and unique rhythmic genes. Taken together, this study further establishes Nematostella as a non-symbiotic model organism to study circadian rhythms and increases our understanding about the fundamental elements of circadian regulation and their evolution within the Metazoa